2012
DOI: 10.1074/jbc.m111.297028
|View full text |Cite
|
Sign up to set email alerts
|

Functional Impact of Heterogeneous Nuclear Ribonucleoprotein A2/B1 in Smooth Muscle Differentiation from Stem Cells and Embryonic Arteriogenesis

Abstract: Background: SMC differentiation is a complicated process involving many transcription factors. Results: hnRNPA2/B1 regulates SMC differentiation gene expression transcriptionally and promotes neural crest cell migration and differentiation toward SMCs. Conclusion: hnRNPA2/B1 promotes smooth muscle differentiation and development in vitro and in vivo. Significance: This is the first report to demonstrate the functional involvements of hnRNPA2/B1 in SMC differentiation from stem cells and embryonic arteriogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 50 publications
5
31
0
Order By: Relevance
“…38,39 Previous data from our laboratory demonstrated that several signal transducers, including Nrf3-Pla2g7/Nox4-induced H 2 O 2 , histone deacetylase 7, and heterogeneous nuclear ribonucleoproteins, serve either as enhancers or inhibitors of stem cell differentiation toward the SMC lineage. [40][41][42][43][44] In the present study, we confirmed that the interaction of integrins α4/α5 and β1 with matrix protein domains of collagen IV is crucial for adventitial stem cell differentiation as identified by blocking peptides for integrin receptors. As our ex vivo data on adventitial stem cell migration into decellularized vessel wall indicated an abundance of cells that expressed smooth muscle markers, it is plausible that the infiltrated progenitor cells were driven toward SMC differentiation as a result of direct contact with matrix proteins within the vessel wall.…”
Section: Discussionsupporting
confidence: 83%
“…38,39 Previous data from our laboratory demonstrated that several signal transducers, including Nrf3-Pla2g7/Nox4-induced H 2 O 2 , histone deacetylase 7, and heterogeneous nuclear ribonucleoproteins, serve either as enhancers or inhibitors of stem cell differentiation toward the SMC lineage. [40][41][42][43][44] In the present study, we confirmed that the interaction of integrins α4/α5 and β1 with matrix protein domains of collagen IV is crucial for adventitial stem cell differentiation as identified by blocking peptides for integrin receptors. As our ex vivo data on adventitial stem cell migration into decellularized vessel wall indicated an abundance of cells that expressed smooth muscle markers, it is plausible that the infiltrated progenitor cells were driven toward SMC differentiation as a result of direct contact with matrix proteins within the vessel wall.…”
Section: Discussionsupporting
confidence: 83%
“…33 have nicely demonstrated that RNAbinding protein HuR attenuates miRNA-mediated repression by promoting miRISC dissociation from the target RNA. Moreover, our previous studies have suggested an important role for another two RBPs, hnRNPA1 11 and hnRNPA2B1, 34 in SMC differentiation. These evidence together with our observation that much less miR-34a and SirT1 3′UTR were loaded into Ago2-RISC complex upon SMC differentiation prompts us to speculate that miR-34a upregulates SirT1 during SMC differentiation through a similar mechanism as reported by Kundu et al 33 In other words, the upregulation of SirT1 by miR-34a may well be a result of RBPs, such as HuR, hnRNPA1 and hnRNPA2B1, interacting with miR-34a-binding sites and/or other elements within the 3′UTR of SirT1 to disengage it from Ago2-RISC complex during differentiation.…”
Section: S Ir T 1 a C T A 2 T A G Lnmentioning
confidence: 89%
“…Detailed protocols for mouse ESCs (mESCs) (ES-D3 cell line, CRL-1934; ATCC, Manassas, VA, USA) culture and SMC differentiation were described in our previous studies. [11][12][13][14]17,22,34,43,44 The Shef-1, 2, 3, 6, and 7 human ESC lines were obtained from the United Kingdom Stem Cell Bank (UKSCB, Hertfordshire, UK) and maintained in our Laboratory as described in our previous study. 18 Briefly, undifferentiated ESCs were dissociated into single cells and seeded onto collagen I/IV (5 μg/ml)-coated flasks or plates in differentiation medium (DM, MEM alpha medium (Gibco, Carlsbad, CA, USA) supplemented with 10% FBS, 0.05 mM 2-mercaptoethanol, 100 U/ml penicillin, and 100 μg/ml streptomycin) for 0-9 days prior to further treatment.…”
Section: S Ir T 1 a C T A 2 T A G Lnmentioning
confidence: 99%
“…[26][27][28][29][30] For instance, 2 hnRNPs (heterogeneous nuclear ribonucleoproteins), hnRNPA1 31 and hnRNPA2B1, 32 have been identified as key molecules for the regulation of VSMC differentiation from embryonic stem cells as it directly binds to promoter regions of VSMC-specific genes and transcription factors such as SRF and myocardin. hnRNPA1 also mediates its effect by recruiting Cbx3 (chromobox protein homolog gene 3), another VSMC differentiation regulatory nuclear protein.…”
Section: Vsmc Origin and Differentiationmentioning
confidence: 99%
“…hnRNPA1 also mediates its effect by recruiting Cbx3 (chromobox protein homolog gene 3), another VSMC differentiation regulatory nuclear protein. 33 Of note, knockdown of hnRNPA2B1 32 or Cbx3 33 was found to inhibit neural crest cell migration and differentiation into VSMCs, resulting in severe developmental defects of brachial arteries and reduced blood circulation in chick embryos. Similarly, a role for reactive oxygen species in regulating gene expression in stem cell-derived VSMCs has been characterized.…”
Section: Vsmc Origin and Differentiationmentioning
confidence: 99%